Qinggan Huoxue Recipe Alleviates Alcoholic Liver Injury by Suppressing Endoplasmic Reticulum Stress Through LXR-LPCAT3 - Lu, Yifei; Shao, Mingmei; Xiang, Hongjiao; Wang, Junmin; Ji, Guang; Wu, Tao (Frontiers in Pharmacology, 2022)
Endoplasmic reticulumstress (ERS) plays a key role in alcohol liver injury(ALI). Lysophosphatidylcholine acyltransferase 3(LPCAT3) is a potential modifier of ERS. It was examined whether the protective effect of QingganHuoxue Recipe (QGHXR) against ALI was associated with LPCAT3 by suppressing ERS from in vivo and in vitro experiment. Male C57BL/6 mice were randomly divided into five groups (n=10, each) and treated for eight weeks as follow: control diet-fed group (Con), Ethanol diet-fed group(EtOH-fed), QGHXR group (QGHXR), Qinggan recipe group (QGR) and Huoxue recipe group (HXR). QGHXR, QGR and HXRgroup attenuated liver injury mainly manifested in reducing serum ALT, AST and liver TG, and reducing the severity of liver cell necrosis and steatosis in ALI mouse models. QGHXR mainly inhibited mRNA levels ofLxrα, Perk, Eif2α, Atf4 and activated mRNA levels of Lpcat3, Ire1α, while inhibited protein levels of LPCAT3, eIF2α, IRE1α, XBP1u and activated protein levels of GRP78 to improve ALI. QGR was more inclined to improve ALI by inhibiting mRNA levels of Lxrα, Perk, Eif2α, Atif4, Chop and activating mRNA levels of Lpcat3, Ire1α while inhibiting protein levels of LPCAT3, PERK, eIF2α, IRE1α, and XBP1u. HXR was more inclined to improve ALI by inhibiting mRNA levels of Perk, Eif2α, Atf4, and Chop mRNA while inhibiting protein levels of LPCAT3, PERK, eIF2α, IRE1α, XBP1u, and activating protein levels of GRP78. Ethanol(100mM) was used to intervene HepG2 and AML12 to establish an ALI cell model and treated by QGHXR, QGR and HXR medicated serum (100mg/L). Mainly respect in decreasing the expression of TG, IL-6 and TNF-α in ALI model cells induced by ethanol .In AML12 cells, QGHXR and its disassembly mainly activated Grp78 mRNA expression together with inhibiting Lxrα, Lpcat3, Eif2α, Atf4, Xbp1 mRNA expression. The protein expression of eIF2α and XBP1u was inhibited, and the expression of PERK and GRP78 was activated to alleviate ALI. In HepG2 cells, QGHXR mainly alleviate ALI by inhibiting the mRNA expression of LPCAT3, CHOP, IRE1α and XBP1andeIF2α, CHOP and IRE1α protein. QGR was more inclined to inhibit the protein expression of PERK, and HXR was more likely to inhibit the protein expression of ATF4.